Still-life Photography as Visual Poetry Media for Social Criticism of Lumpur Lapindo - Yulius Widi Nugroho (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2022)
Visual media photography is prioritized to present actual and factual information as news media and art media, and Visual Poetry is a work of art that combines two visual and verbal media as one work. The purpose of this research is to make still life photography works and the meaning of photo works as a medium for Visual Poetry. The object of the photo is about the condition of the Lapindo Mud on Porong Sidoarjo Indonesia, which has been neglected for years without serious handling. This creation method uses a photographic method of photographing natural objects. Methods of collecting data by observation, interviews, and documentation offline and online. The discussion of meaning uses the semiotic theory of Roland Barthes. The result of this creation is to capture visual phenomena which are then converted into words and finally assembled into poetry. The meaning of the final work of the photo comes from the visual and verbal media that are presented together, and of course it remains open to meaning that is free from the audience. Visual Poetry's work is used as a social critique of the condition of the Lapindo Mud which is physically and socially neglected. The conclusion of this creation is that visual and verbal media have their respective advantages and limitations, but can be combined into new works and new meanings. The benefit of the creation of this work is the development of methods of visual meaning that can produce new art media.